Prevalence of Anaemia in Children Diagnosed with Pneumonia in a Tertiary Hospital in Quito, Ecuador - Garrido Salazar, David Israel; Fuseau, Michelle; Garrido, Santiago Moises; Vivas, Gina; Gutiérrez, Miguel (Journal of Nepal Paediatric Society, 2019)
Introduction: Anaemia and pneumonia are frequent diseases which affect children. However, these two conditions could coexist. The aim of this study is presenting the prevalence of anemia among Ecuadorian children diagnosed with pneumonia, hospitalized in a tertiary hospital. Material and Methods: An observational and cross-sectional study conducted through a secondary source in that 80 children, between six months and 15 years of age were included. All the patients involved were admitted to the paediatric department presenting pneumonia. The medical evaluation included anthropometric measurements and complete blood count. Risk associations were evaluated using odds ratio. Results: Anaemia was found in 21.25% of the whole group. Nonetheless, the children under three years of age were more affected by this condition (18.75%). Low mean corpuscular volume and high red cells distribution width were more frequent than anaemia itself; 38.75% and 28.75%, respectively. Additionally, the prevalence of anaemia in children under 36 months was higher than the patients with over three years, with a significant risk of anaemia in the first group (OR 13.04; CI 95% 11.48-14.61; p<0.05) and low haematocrit (OR 14.64; CI 95% 12.53-16.75; p<0.05). This was also seen in low mean corpuscular volume (OR 3.23; CI 95% 2.3-4.17; p<0.05), high red cells distribution width (OR 2.77; CI 95% 1.76-3.78; p<0.05), and mean corpuscular haemoglobin (OR 8.48; CI 95% 7.14-9.82; p<0.01). Conclusions: Anaemia is a frequent condition in paediatric pneumonia, particularly during the first three years of life. Therefore, anaemia or nutritional deficiencies could be a risk factor for respiratory diseases.